2021
DOI: 10.1021/acs.jpca.0c08760
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of Actinyl Ion Complexation with Dipyriamethyrin Macrocyclic Ligands

Abstract: Relativistic density functional theory has been employed to characterize [AnO2(L)]0/‑1 complexes, where An = U, Np, Pu, and Am, and L is the recently reported hexa-aza porphyrin analogue, termed dipyriamethyrin, which contains six nitrogen donor atoms (four pyrrolic and two pyridine rings). Shorter axial (AnO) and longer equatorial (An–N) bond lengths are observed when going from AnVI to AnV. The actinide to pyrrole nitrogen bonds are shorter as compared to the bonds to the pyridine nitrogens; the former also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 80 publications
2
30
0
Order By: Relevance
“…Quantifying the extent of covalent bonding involving the actinide (An) 5f shell and different donor ligands is at the forefront of actinide chemistry research. Actinide selectivity of extraction reagents is typically associated with a degree of 5f covalent bonding when compared to 4f bonding of the lanthanide (Ln) analogues. Identifying and quantifying covalency in the An–ligand bonding is therefore essential for solving practical problems encountered, for instance, in the nuclear fuel cycle. 5f covalency is also a fascinating topic on its own that has attracted much interest in the chemistry community, as evidenced by many publications (refs and other articles cited herein represent a selection).…”
Section: Introductionmentioning
confidence: 99%
“…Quantifying the extent of covalent bonding involving the actinide (An) 5f shell and different donor ligands is at the forefront of actinide chemistry research. Actinide selectivity of extraction reagents is typically associated with a degree of 5f covalent bonding when compared to 4f bonding of the lanthanide (Ln) analogues. Identifying and quantifying covalency in the An–ligand bonding is therefore essential for solving practical problems encountered, for instance, in the nuclear fuel cycle. 5f covalency is also a fascinating topic on its own that has attracted much interest in the chemistry community, as evidenced by many publications (refs and other articles cited herein represent a selection).…”
Section: Introductionmentioning
confidence: 99%
“…The contraction was proven to be driven by the decrease in the ionic radius. [154][155][156] Other studies indicated increasing 5f covalency in the An-O yl bonds toward Pu. [157][158][159] Calculated and experimental XANES spectra are shown in Fig.…”
Section: Dalton Transactionsmentioning
confidence: 97%
“…53,54 We have recently reported the favorable bonding features between dipyriamethyrin and other AnO 2 n + (An = Np, Pu and Am; n = 1, 2) ions in gaseous and CH 2 Cl 2 media. 55 However, the understanding of the complexing ability of the dipyriamethyrin ligand with minor actinides as dioxocations remains unexplored.…”
Section: Introductionmentioning
confidence: 99%